2019
DOI: 10.1038/s41557-019-0327-5
|View full text |Cite
|
Sign up to set email alerts
|

On-water surface synthesis of crystalline, few-layer two-dimensional polymers assisted by surfactant monolayers

Abstract: Despite rapid progress in recent years, it has remained challenging to prepare crystalline twodimensional polymers. Here, we report the controlled synthesis of few-layer 2D polyimide crystals on the water surface, through reaction between amine and anhydride monomers, assisted by surfactant monolayers. We obtained 2D polymers with high crystallinity, a thickness of approximately 2 nm, and an average crystal domain size of around 3.5 μm 2. The molecular structure of the materials, their grain boundaries, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
261
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 306 publications
(282 citation statements)
references
References 39 publications
1
261
0
11
Order By: Relevance
“…When the macromolecular dye is loaded into PI-COF-3, the temperature dependence in the emission spectrum is studied. Then we found that the product had unique luminous properties that Yes Yes [40,45] vary with temperature, indicating that dye-doped PI-COFs can be applied for temperature sensor devices.…”
Section: Adsorption and Separationmentioning
confidence: 91%
See 2 more Smart Citations
“…When the macromolecular dye is loaded into PI-COF-3, the temperature dependence in the emission spectrum is studied. Then we found that the product had unique luminous properties that Yes Yes [40,45] vary with temperature, indicating that dye-doped PI-COFs can be applied for temperature sensor devices.…”
Section: Adsorption and Separationmentioning
confidence: 91%
“…In recent years, researchers have been working hard to explore low-cost and large-scale synthesis methods, such as solvothermal synthesis, [17,18,26,27,41,42,44,46,48] condensation polymerization synthesis, [25,45] high-temperature solid-state synthesis, [39] interfacial synthesis, and ionothermal synthesis. [40,45]…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…2D monolayer organic crystals are usually fabricated by solution‐processed methods at water/air interface, [ 14–22 ] where water surface is usually used to control the diffusion of organic solvent and serves as a substrate for the self‐assembly of organic molecules due to its relatively high surface tension and molecularly flat surface. Langmuir–Blodgett (LB) technique has been previously applied for the fast and simple fabrication of organic monolayer crystals at water/air interface.…”
Section: Figurementioning
confidence: 99%
“…Very recently, our group reported a surfactant‐monolayer‐assisted interfacial synthesis (SMAIS) of few‐layer 2D polyimide and 2D polyamide films on water surface . Nevertheless, the achieved 2D polyimide film showed abundant amorphous areas (≈40 % ratio) interconnected within crystalline domains.…”
Section: Introductionmentioning
confidence: 99%